Investment protected cell companies - Yasir Altaee; Mustafa ALnasri (الرافدین للحقوق, 2023)
The investment business is in a continuous and continuous development and permanent renewal, and this stems from the nature of the commercial and investment business and the practical reality need for such change. These developments also came to the commercial companies sector, so that in some countries a new form of companies appears in addition to the types of companies known classically, so that the new companies are of special purposes in accordance with the law regulating them.Indeed, the so-called protected cell companies appeared in a number of countries, including the Kingdom of Bahrain, which aims, in terms of its purposes, for this company to carry out a specific set of financial or investment activities that fall under the supervision of the Central Bank in the country. The idea in this type of company is that it is established from several investment cells that represent a special investment fund and one central board of directors instead of establishing a fund company for a specific type of investment and establishing another fund company for investment of another type , as this company will provide a collection of these funds and various investment activities in several investment cells independent from the other within one company. This company is one of the investment companies, as it consists of a group of cells, each cell has a specific investment purpose, and each cell is considered separate in itself, so that if this cell loses, the rest of the cells remain continuous and not affected by it.The existence of such a type of company with legally defined purposes will lead to the provision of great investment opportunities in specific and specific areas, and through the expansion of investment tools in the state.